How membrane structures control T cell signaling. - Lillemeier, Björn F.; Klammt, Christian (Frontiers in Immunology, 2012)
Genetic and biochemical studies have identified a large number of molecules involved in T cell signalling. They have provided us with a comprehensive understanding of protein-protein interactions and protein modifications that take place upon antigen recognition. Diffraction limited fluorescence microscopy has been used to study the distribution of signaling molecules on a cellular level. Specifically, the discovery of microclusters (MCs) and the immunological synapse (IS) demonstrates that T cell signaling cascades utilizes spatial association and segregation. Recent advancements in live cell imaging have allowed us to visualize the spatio-temporal mechanisms of T cell signaling at nanometer scale resolution. This led to the discovery that proteins are organized in distinct membrane domains prior and during T cell activation. Evidently, plasma membrane structures and signaling molecule distributions at all length scales (molecular to cellular) are intrinsic to the mechanisms that govern signaling initiation, transduction and inhibition. Here we provide an overwiew of possible plasma membrane models, molecular assemblies that have been described to date, how they can be visualized and how they might contribute to T cell signaling.